(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1858)
This article discusses the baths discovered at Edzell Castle in Angus in May 1855. The author gives an overview of the ruins and confidently dates their construction to the late sixteenth or early seventeenth century.